1999
DOI: 10.1038/sj.bjc.6690616
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the K-Ras oncogene in an invasive colon cancer cell line down-regulates urokinase receptor expression and plasminogen-dependent proteolysis

Abstract: SummaryThe urokinase receptor, overexpressed in invasive colon cancer, promotes tumour cell invasion. Since K-Ras is activated in many colon cancers, we determined if urokinase receptor overexpression is a consequence of this activated oncogene. Accordingly, urokinase receptor expression was compared in HCT 116 colon cancer cells containing either a mutation-activated K-Ras or disrupted for this oncogene (by homologous recombination). HCT 116 cells containing the disrupted K-Ras oncogene expressed between 50 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…For example, transfection of NIH-3T3 fibroblast cells with constitutively active H-Ras stimulates uPAR transcription about 4-fold, 18 while disruption of mutated K-ras by homologous recombination downregulates uPAR expression. 19 These data provide evidence that the Ras oncogene is a regulator of uPAR expression. Furthermore, treatment with an antisense oligonucleotide against ERK-1/2 or with the inhibitor PD098059 against MEK in transformed PDV keratinocyte cells carrying a mutated H-Ras inhibited uPA synthesis.…”
mentioning
confidence: 73%
“…For example, transfection of NIH-3T3 fibroblast cells with constitutively active H-Ras stimulates uPAR transcription about 4-fold, 18 while disruption of mutated K-ras by homologous recombination downregulates uPAR expression. 19 These data provide evidence that the Ras oncogene is a regulator of uPAR expression. Furthermore, treatment with an antisense oligonucleotide against ERK-1/2 or with the inhibitor PD098059 against MEK in transformed PDV keratinocyte cells carrying a mutated H-Ras inhibited uPA synthesis.…”
mentioning
confidence: 73%
“…We, therefore, asked as to whether Pdcd4 is able to regulate u-PAR gene expression at the promoter level. In GEO cells being characterized by high endogenous Pdcd4 and low endogenous u-PAR (Allgayer et al, 1999b;Allgayer et al, 1999c) a siRNA specifically downregulating endogenous Pdcd4 led to a significant increase of activity of a luciferase reporter driven by À398 bp upstream of the main transcriptional initiation site of the u-PAR gene (Figure 3a). The À398 bp corresponds to the basal u-PAR promoter as described previously (Lengyel et al, 1996;Allgayer et al, 1999c).…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work, we had shown that a motif spanning region À152/À135 of the u-PAR promoter bound by an AP-2-like transcription factor, Sp3 and Sp1, was required for a high u-PAR gene expression in cultured colon cancer cells, the AP-2-like protein mediating a high constitutive and PMA-inducible expression, Sp1, a high u-PAR gene expression caused by the c-src-oncogene (Gallick and Jessup, 1992;Allgayer et al, 1999a, c). Another AP-1 consensus motif (À190/À171) regulates constitutive and phorbol ester-induced u-PAR gene expression in colon cancer, as well as u-PAR gene expression brought about by mutation-activated K-ras (Lengyel et al, 1996;Allgayer et al, 1999b). A PEA3/etssilencer-motif further upstream (at À248 bp) mediates a downregulation of u-PAR gene expression by b 3 -integrin.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on the activation of uPAR transcription by Ras as it is a point of convergence for diverse extracellular signal-stimulated pathways and frequently su ers activating mutations in a wide range of cancers. In addition, the introduction of oncogenic Ras into cells increases extracellular protease activity in general and the expression of uPAR in particular (Westermark and KaÈ haÈ ri, 1999; Lengyel et al, 1995;Jankun et al, 1991;Allgayer et al, 1999;Janulis et al, 1999;Muller et al, 2000). The work of White et al (1995) established that the activation of multiple-ras e ector pathways is necessary to induce cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the growth factor-and cytokineactivated signalling pathways that control uPAR transcription converge on the small GTP-binding protein Ras (Aguirre-Ghiso et al, 1999a). The ras genes (H-ras, N-ras and K-ras) frequently acquire activating mutations in human cancers (Bos, 1998;Hunter, 1997;Yamamoto et al, 1999) and at least HRas and K-Ras have been demonstrated to activate uPAR gene transcription (Aguirre-Ghiso et al, 1999a;Allgayer et al, 1999;Muller et al, 2000). This suggests a mechanism whereby the activity of oncogenic Ras can be linked to the increased invasiveness of malignant cells through the uPA/uPAR proteolytic system.…”
Section: Introductionmentioning
confidence: 99%